Pengaruh Terak Baja Dan Bokashi Sekam Padi Terhadap Sifat Fisika Tanah Pada Andisol - Rina Devnita; R Hudaya; F Rosana (Agrologia, 2014)
Andisols are considered as productive soils, but their P-retention have to be reduced to increase the available P.  This research concerning the remediation of Andisols with steel slag and bokashi of husk to overcome the P problem and to investigate their  influence  to soil physical aspects.  The treatments were arranged in Randomized Block Designed in factorial pattern with two factors: steel slag and bokashi of husk, consisted of four level: 0, 2.5, 5.0 and 7.5 % of soil weight (w/w). The treatments were repeated twice, brought a combination of 4 x 4 x 2.  The soils with each treatments were mixed thoroughly, filled into the polybags, watered to the field capacity, closed tightly, incubated for four months, and sampled for chemical and physical analyses. The parameters were P-retention, bulk density, permeability and aggregate stability.  The result showed that steel slag and bokashi of  husk were interacted in decreasing P-retention.  These combination had no effect to soil physical characteristics which mean that the treatments did not aggravate the bulk density, soil permeability and aggregate stability. The remediation of Andisol with steel slag and bokashi of husk decreased the P-retention, and kept the good aspects of soil physical characteristics.